Second-Generation Lignocellulosic Supportive Material Improves Atomic Ratios of C:O and H:O and Thermomechanical Behavior of Hybrid Non-Woody Pellets - Moreira, Bruno Rafael de Almeida [UNESP]; Viana, Ronaldo da Silva [UNESP]; Cruz, Victor Hugo [UNESP]; Magalhães, Anderson Chagas [UNESP]; Miasaki, Celso Tadao [UNESP]; Figueiredo, Paulo Alexandre Monteiro de [UNESP]; Lisboa, Lucas Aparecido Manzani [UNESP]; Ramos, Sérgio Bispo [UNESP]; Sánchez, Douglas Enrique Juárez [UNESP]; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP]; May, André (MDPI, 2020)
Pellets refer to solid biofuels for heating and power. The pellet's integrity is of great relevant to ensure safe and effective transportation and storage, and comfort to stakeholders. Several materials that are supportive, whether organic and inorganic, to pellets exist. However, no work in the literature is linking making hybrid non-wood pellets with addition of residual biomass from distillation of cellulosic bioethanol, and this requires further investigations. Figuring out how effective this challenging agro-industrial residue could be for reinforcing non-wood pellets is accordingly the scientific point of this study focusing on management of waste and valorization of biomass. The pilot-scale manufacturing of hybrid pellets consisted of systematically pressing sugarcane bagasse with the lignocellulosic reinforcement at the mass ratios of 3:1, 1:1, and 1:3 on an automatic pelletizer machine at 200 MPa and 125 °C. Elemental contents of C and H, durability, and energy density all increased significantly from 50.05 to 53.50%, 5.95 to 7.80%, 95.90 to 99.55%, and 28.20 to 31.20 MJ kg-1, respectively, with blending the starting material with the reinforcement at 1:3. Preliminary evidence of residual biomass from distillation of second-generation bioethanol capable of highly improving molecular flammable/combustible properties, mechanical stability, and fuel power of composite non-wood pellets exist.
Keywords: blending; cellulosic bioethanol; energy storage; fuel grade biosolids; natural binding agent; reinforcement; sustainable waste-to-energy technique